2005
DOI: 10.1111/j.1365-2958.2005.04805.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase II as a fidelity factor in chromosomal DNA synthesis in Escherichia coli

Abstract: SummaryEscherichia coli DNA polymerase III holoenzyme (HE) is the main replicase responsible for replication of the bacterial chromosome. E. coli contains four additional polymerases, and it is a relevant question whether these might also contribute to chromosomal replication and its fidelity. Here, we have investigated the role of DNA polymerase II (Pol II) ( polB gene product). Mismatch repair-defective strains containing the polBex1 allele -encoding a polymerase-proficient but exonucleolytically defective P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
84
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(98 citation statements)
references
References 60 publications
(101 reference statements)
9
84
1
Order By: Relevance
“…15 DNA polymerases Pol II, Pol IV and Pol V serve as accessory enzymes. [16][17][18] The primary function for Pol II is remains unclear, but it has been suggested that Pol II may serve as a backup enzyme for Pol III 16 and re-initiates DNA synthesis in UV-irradiated E. coli cells. 19 Like Pol III and Pol I, Pol II is considered a high fidelity enzyme due to its proofreading exonuclease activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 DNA polymerases Pol II, Pol IV and Pol V serve as accessory enzymes. [16][17][18] The primary function for Pol II is remains unclear, but it has been suggested that Pol II may serve as a backup enzyme for Pol III 16 and re-initiates DNA synthesis in UV-irradiated E. coli cells. 19 Like Pol III and Pol I, Pol II is considered a high fidelity enzyme due to its proofreading exonuclease activity.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 In some circumstances UPEC rapidly replicates in intracellular bacterial communities (IBC), a biofilm-like state observed in animal and human infections. 3,5 UPEC may also chronically persist in the epithelium (16).…”
Section: Introductionmentioning
confidence: 99%
“…We used alleles of DNA Pol IV (DinB) ( Table 3) and the dnaE915 allele (21,22), an antimutator allele that reduces DinB-dependent mutations (23,24). Thus, we hypothesized that genetic interactions between dnaE915 and dinB variants should result in detectable changes in DinB-dependent phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Pol III␣(915) is an antimutator either because it synthesizes DNA slower than the native replicative DNA polymerase active subunit, DNA Pol III␣ (21,22), or because it might inhibit low-fidelity DNA synthesis by TLS DNA polymerases, specifically DinB (23). Its antimutator activity is also dependent upon another TLS DNA polymerase, DNA Pol II, which likely prevents mutagenesis generated by DinB (24). This genetic system has permitted us to discover key DinB residues that mapped to specific areas of DinB, allowing us to gain insights into the mechanisms underlying the DinB-mediated overproduction loss-of-survival phenotype.…”
mentioning
confidence: 99%
“…E. coli has five DNA polymerases. Pol I, Pol II and Pol III have essentially higher fidelity than Y-family polymerases Pol IV and Pol V. The high fidelity DNA polymerases play an important role in normal DNA replication and in SOS-induced DNA repair [116,137,138]. Although error-prone Pol IV is also involved in the DNA repair activated by SOS response, several studies also suggest that Pol IV functions in implementation of the mutator phenotype.…”
Section: Y Family Polymerasesmentioning
confidence: 99%